Explanation of Effective Indicators on Social Sustainable Development with Emphasis on the Complete Streets Approach - Zahra Tahmasbnia; Abolfazl Dehghanmongabadi (توسعه پایدار شهری)
In recent decades, due to the increase in urban population and the unbridled growth of urbanization and urbanism, many efforts have been made to create livable cities by emphasizing the place of sustainable public open spaces. Streets are one of the most important components of public spaces, and in recent years’ special attention has been paid to the design and planning of these spaces. One of the important principles of livable cities is to pay special attention to the topics related to their social aspects, that urban streets can provide ideal spaces for increasing social interactions and developing social sustainability, according to their places inside cities. In the last two decades, the approach of complete streets based on the design of sustainable streets has been proposed in the world, which provides a new perspective on designing and planning of streets. In this regard, the main goal of this study is to identify indicators that influence on the social sustainable development in urban streets with an emphasis on the approach of complete streets. The research method used in this study in the form of an interpretative paradigm, among the qualitative research methods, is the Scoping Review method. In this research, an attempt has been made to answer the questions raised by carefully examining the limited available studies based on Arksey & O'Malley method. Finally, according to the obtained results, identified indicators can be classified into groups including physical factors, safety and security, economic factors, social and environmental factors. According to the identified factors, suggestions have been made to strengthen social sustainable development in urban streets with emphasis on the approach of complete streets.